The deterrence effect of linear versus convex fines: Laboratory evidence - Marcelo Caffera; Carlos Chávez Rebolledo; Analía Ardente (Journal of Applied Economics, 2021)
Using experiments in which participants play the role of polluting firms, we study compliance behavior with emissions limits under two types of fines and two different regulatory instruments. We find that the market price of pollution permits and the probability of violating permits holdings are higher with a fine that is convex in the level of violation than with one that is linear. This effect operates through an increase in the prices asked by sellers, not in the bids made by the buyers of permits. We do not observe an effect of the type of the fine on the average level of violation or the number of firms in violation in the case of emission standards. We conclude that the type of fines may affect the cost-effectiveness of pollution control programs based on tradable pollution permits.
Keywords: 330; enforcement; Environmental policy; laboratory experiments; penalty structure